2021
DOI: 10.1186/s12903-021-01998-y
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis as a risk for oral cancer: a case–control study

Abstract: Background The aetiology of oral cancer is multifactorial, as various risk factors (genetics, socioeconomic and lifestyle factors) contribute to its development. Data in the literature suggest that people with periodontal disease have an increased risk of developing oral cancer, and the severity of periodontitis correlates with the appearance of oral squamous cell carcinoma. The aim of this study was to revise the non-genetic risk factors that may influence the development of OC, while focusing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…Likewise, OPC mortality rates in males are expected to decline at the end of the period, while in females they will stabilize, except in those > 65 years where mortality rates are expected to rise. Therefore, our findings emphasized the need to maintain educational interventions aimed at the entire population in the coming years, promoting smoking cessation and alcohol abstinence, vaccination against HPV, campaigns for early diagnosis of potential malignant lesions in the oral cavity and oropharynx, changes in lifestyle, preservation of oral hygiene and periodontal health [17], and high consumption of fruits and vegetables. Our predictive model indicated that these preventive programs should be intensified especially in females in the near future.…”
Section: Discussionmentioning
confidence: 87%
“…Likewise, OPC mortality rates in males are expected to decline at the end of the period, while in females they will stabilize, except in those > 65 years where mortality rates are expected to rise. Therefore, our findings emphasized the need to maintain educational interventions aimed at the entire population in the coming years, promoting smoking cessation and alcohol abstinence, vaccination against HPV, campaigns for early diagnosis of potential malignant lesions in the oral cavity and oropharynx, changes in lifestyle, preservation of oral hygiene and periodontal health [17], and high consumption of fruits and vegetables. Our predictive model indicated that these preventive programs should be intensified especially in females in the near future.…”
Section: Discussionmentioning
confidence: 87%
“…The findings from our work also connected to the literature of periodontal disease. Periodontitis has been posited as a risk factor for oral cancer (Komlós et al, 2021 ). In connection with the preceding paragraph, species from Fusobacterium have been identified as having associations with periodontitis (Mohanty et al, 2019 ).…”
Section: Analysis Of Results and Discussionmentioning
confidence: 99%
“…Actually, the causative and promotion role of P. gingivalis in oral cancers and in OSCC appears confirmed in recent reports and meta-analyses ( 24 , 25 ). As P. gingivalis is the major causative microbial agent of periodontitis ( 26 ), therefore its association with oral cancers pertains to the direct association with previous gum and dental hygiene impairments leading to periodontitis ( 5 , 27 ), and this may be beyond the purpose of our report.…”
Section: The Oral Microbiome Composition In the Hygiene Perspective O...mentioning
confidence: 93%
“…Moreover, teeth and gums associated pathologies, e.g. periodontitis, seem to be a leading cause of oropharyngeal cancers, although lifestyle and voluptuary habits, associated with age, sex, smoke, tobacco and alcohol abuse, have to be included in the causative group of factors ( 5 ).…”
Section: Introductionmentioning
confidence: 99%